DOES ARTICLE 170-A OF THE NATIONAL TAX CODE ALSO APPLY TO UNDUE TAX PAYMENTS ARISING FROM UNCONSTITUTIONALITY? (CIPEEX, 2025)
This article examines whether the prohibition of set-off in Article 170-A of Brazil’s National Tax Code extends to undue tax payments resulting from unconstitutional norms, in light of the requirement of a final and unappealable judgment for credit recognition. It is a doctrinal, exploratory analysis grounded in bibliographic research and in decisions from the Supreme Federal Court and the Superior Court of Justice. The objective is to delimit the scope of Article 170-A when taxes were collected under a statute later declared unconstitutional and to assess the implications for the principles of legal certainty, legality, and the prohibition of confiscation. The method adopts a systematic reading of the Code and the Constitution aligned with the provision’s teleology—preventing set-offs based on decisions still subject to reversal and preserving fiscal stability. The results show that the Superior Court of Justice has predominantly required res judicata for all tax credits, including those stemming from a declaration of unconstitutionality, whereas part of the scholarship advocates immediate refund or set-off when unconstitutionality has been recognized with erga omnes and binding effect. The conclusion is that the res judicata requirement serves a cautionary function but must be construed consistently with the Constitution so as not to frustrate the protective purpose of Article 170-A, ensuring effective refunds and predictability through case-law uniformization.
Keywords: refund of undue payment; unconstitutionality; Article 170-A of the National Tax Code; tax set-off